1997
DOI: 10.1128/mcb.17.4.1947
|View full text |Cite
|
Sign up to set email alerts
|

Megakaryocytic Differentiation Induced by Constitutive Activation of Mitogen-Activated Protein Kinase Kinase

Abstract: The K562 erythroleukemia cell line was used to study the molecular mechanisms regulating lineage commitment of hematopoietic stem cells. Phorbol esters, which initiate megakaryocyte differentiation in this cell line, caused a rapid increase in extracellular-signal-regulated kinase (ERK), which remained elevated for 2 h and returned to near-basal levels by 24 h. In the absence of extracellular stimuli, ERK could be activated by expression of constitutively active mutants of mitogen-activated protein (MAP) kinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
184
3
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(205 citation statements)
references
References 58 publications
16
184
3
2
Order By: Relevance
“…In contrast to NGF treatment, epidermal growth factor (EGF) treatment of PC12 cells induced an acute phasic activation of p42 MAPkinase which returned to baseline within 30 min ( Figure 1B). These data are in agreement with data of several other laboratories [16,21,22,34,35]. Bailie et al reported that primary cultures of hepatocytes possess binding sites for NGF, and we investigated whether NGF had a similar capability to modulate the MAP kinase cascade in these cells [26].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In contrast to NGF treatment, epidermal growth factor (EGF) treatment of PC12 cells induced an acute phasic activation of p42 MAPkinase which returned to baseline within 30 min ( Figure 1B). These data are in agreement with data of several other laboratories [16,21,22,34,35]. Bailie et al reported that primary cultures of hepatocytes possess binding sites for NGF, and we investigated whether NGF had a similar capability to modulate the MAP kinase cascade in these cells [26].…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, the role of signalling by the MAP kinase cascade in terms of either cellular proliferation or cellular differentiation is currently under intensive study and recent reports using other cell types have suggested a role for chronic MAP kinase activation in causing exit from the cell cycle followed by cellular differentiation [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, PMA caused a rapid increase in ERK1 activity which paralleled the elevation in JNK activity. The involvement of the c-Raf-1-ERK signaling cascade in the modulation of gene expression by this phorbol ester is well established (Jones et al, 1994;Masuelli and Cutler, 1996;Whalen et al, 1997;de Vries-Smits et al, 1992;Bogoyevitch et al, 1995;Cai et al, 1997;Sozeri et al, 1992;Berra et al, 1995). These observations, combined with our unpublished ®nding that anisomycin, a selective activator of the JNKs (Bogoyevitch et al, 1995;Cano et al, 1994), does not increase u-PAR display, makes it likely that the propagation of the PMA stimulus to the nuclear transcriptional machinery regulating u-PAR expression is dependent on the cooperation of both JNK1-and ERK-dependent signaling modules.…”
Section: Discussionmentioning
confidence: 99%
“…However, a prevailing view is that the ability of phorbol ester to alter inducible gene expression is mediated through the classical signaling module (cRaf-1-ERK) and several observations by other investigators have supported this view. Thus, PMA induces ERK activity in a number of systems (Jones et al, 1994;Masuelli and Cutler, 1996;Whalen et al, 1997;de Vries-Smits et al, 1992;Bogoyevitch et al, 1995;Cano et al, 1995) and the co-expression of kinase-defective ERK1/ERK2 expression constructs inhibits the PMA-dependent stimulation of AP-1-regulated gene expression (Frost et al, 1994). Further, Protein Kinase C, the receptor for PMA, binds to and activates c-Raf-1 leading to ERK activation (Cai et al, 1997;Marquardt et al, 1994;Sozeri et al, 1992;Berra et al, 1995;Sauma and Friedman, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in some systems the platelet-derived growth factor (PDGF) stimulates sustained ERK activity and results in S-phase entry or cell differentiation whereas epidermal growth factor (EGF) stimulates transient ERK activity that does not drive cells in to S-phase and does not promote cell differentiation [204][205][206][207]. Duration and strength dependent modulation of cell fate appear to operate in neuronal PC12 cells, NIH3T3 fibroblasts [208], macrophages [209] and lymphocytes [210,211]. It is becoming apparent that cell fates determined by different growth factors that activate the same MAPK components requires a spatiotemporal control of MAPK targeting, sequestration and activation.…”
Section: Multiple Erk Scaffolds Regulate the Diverse Functions Of Thementioning
confidence: 99%